2021
DOI: 10.3390/microorganisms10010062
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing Characterization of Virulence Profiles of Listeria monocytogenes Food and Human Isolates and In Vitro Adhesion/Invasion Assessment

Abstract: Listeria monocytogenes (Lm) is the causative agent of human listeriosis. Lm strains have different virulence potential. For this reason, we preliminarily characterised via Whole-Genome Sequencing (WGS) some Lm strains for their key genomic features and virulence-associated determinants, assigning the clonal complex (CC). Moreover, the ability of the same strains to adhere to and invade human colon carcinoma cell line Caco-2, evaluating the possible correspondence with their genetic virulence profile, was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…LIP-I is composed of important virulence genes (including act A, hly, mpl , plc A, plc B, prf A and orf X) and is necessary for intracellular survival and spread from cell to cell [ 35 ]. LPI-1 is typically present in all L. monocytogenes strains [ 2 , 41 ]. This actA -negative deer carcass isolate (with VP3b, SG IIa and ST412) also missed the lap B (coding for an adhesion protein) and vip (coding for an invasion protein) genes, indicating a reduced virulence in this isolate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LIP-I is composed of important virulence genes (including act A, hly, mpl , plc A, plc B, prf A and orf X) and is necessary for intracellular survival and spread from cell to cell [ 35 ]. LPI-1 is typically present in all L. monocytogenes strains [ 2 , 41 ]. This actA -negative deer carcass isolate (with VP3b, SG IIa and ST412) also missed the lap B (coding for an adhesion protein) and vip (coding for an invasion protein) genes, indicating a reduced virulence in this isolate.…”
Section: Discussionmentioning
confidence: 99%
“…How the absence of these two genes affects the virulence of L. monocytogenes IVb isolates needs to be further studied. Typically, ST1 (CC1) and ST4 (CC4) have been associated with clinical cases more often than other STs [ 35 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Listeria monocytogenes strains may carry the llsA , llsB , llsD , llsG , llsH , llsP , llsX, and llsY genes, together designated LIPI-3 [ 5 ]. Pathogenicity studies in murine models indicated that LIPI-3 was responsible for the increased virulence of some strains of the pathogen [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This pathogen is characterized by great genetic diversity and variability in virulence potential [ 5 ]. Consequently, L. monocytogenes isolates originating from food belong to different molecular groups, evolutionary lineages, sequence types (ST), and clonal complexes (CC) [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation